Nutrition knowledge and attitude of participants and non-paticipants in the 1974-75 Nutrition School of the Air - Quimpo, Catherine F.
In 1974, the Food and Nutrition Research Institute, NSDB conducted its third Nutrition School of the Air. Unlike the past Schools, the present study used both radio and the Liwayway magazine. This study sought to compare the nutrition knowledge and attitude of two groups of subjects: those who participated in the School and their non-participating neighbors. On the basis of the t-test, the participants were found to have significantly better nutrition knowledge and attitude scores than the non-participants. However, the data suggest that these differences may be due not only to their attendance in the School but also to the extent of use of other media channels. The study did not show a significant correlation between knowledge and attitude. The participants were divided into three groups depending on whether they used radio, print, or both. The analysis of variance for differences in methods did not show significant differences in knowledge scored among the three groups. However, there were no significant differences in attitude scores between users of radio or print and those who used both. Socio-economic factors were related to the nutrition knowledge and attitude of the respondents. Among these factors, education and media habits, specifically magazine readership were the most significantly related.